The burden of Legionnaires' disease in New Zealand (LegiNZ): a national surveillance study. Issue 7 (July 2019) - Priest, Patricia C; Slow, Sandy; Chambers, Stephen T; Cameron, Claire M; Balm, Michelle N; Beale, Mark W; Blackmore, Timothy K; Burns, Andrew D; Drinković, Dragana; Elvy, Juliet A; Everts, Richard J; Hammer, David A; et al.
Summary: Background: Legionnaires' disease is under-diagnosed because of inconsistent use of diagnostic tests and uncertainty about whom to test. We assessed the increase in case detection following large-scale introduction of routine PCR testing of respiratory specimens in New Zealand. Methods: LegiNZ was a national surveillance study done over 1-year in which active case-finding was used to maximise the identification of cases of Legionnaires' disease in hospitals. Respiratory specimens from patients of any age with pneumonia, who could provide an eligible lower respiratory specimen, admitted to one of 20 participating hospitals, covering a catchment area of 96% of New Zealand's population, were routinely tested for legionella by PCR. Additional cases of Legionnaires' disease in hospital were identified through mandatory notification. Findings: Between May 21, 2015, and May 20, 2016, 5622 eligible specimens from 4862 patients were tested by PCR. From these, 197 cases of Legionnaires' disease were detected. An additional 41 cases were identified from notification data, giving 238 cases requiring hospitalisation. The overall incidence of Legionnaires' disease cases in hospital in the study area was 5·4 per 100 000 people per year, and Legionella longbeachae was the predominant cause, found in 150 (63%) of 238 cases. Interpretation: The rate of notified disease during the study period was three-times the average over the preceding 3 years. Active case-finding through systematic PCR testing better clarified the regional epidemiology of Legionnaires' disease and uncovered an otherwise hidden burden of disease. These data inform local Legionnaires' disease testing strategies, allow targeted antibiotic therapy, and help identify outbreaks and effective prevention strategies. The same approach might have similar benefits if applied elsewhere in the world. Funding: Health Research Council of New Zealand.